2014
DOI: 10.1097/dss.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Complication After Pincer Nail Treatment Using a Shape-Memory Alloy

Abstract: Pemphigus refers to a group of rare autoimmune bullous diseases that affect the skin and mucous membranes causing flaccid intraepidermal blisters, erosions, and acantholysis. The 3 major groups of pemphigus are PV, PF, and paraneoplastic pemphigus. Pemphigus vulgaris, the most common form of pemphigus, is caused by IgG autoantibodies directed against desmosomal proteins, specifically desmoglein 3. The presence of IgG autoantibodies against DSG1 and DSG3 can be used to confirm the diagnosis. The mean age of ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The device was removed after 10 days but can stay for 2 or 3 weeks depending on the toenail changes [14]. Thereafter, in 2014, Lee et al used this treatment for a single case, and 4 weeks after surgery, skin necrosis developed on the back of the toe [25]. They concluded that it was caused by local infection from self-adherent bandages.…”
Section: Thementioning
confidence: 99%
“…The device was removed after 10 days but can stay for 2 or 3 weeks depending on the toenail changes [14]. Thereafter, in 2014, Lee et al used this treatment for a single case, and 4 weeks after surgery, skin necrosis developed on the back of the toe [25]. They concluded that it was caused by local infection from self-adherent bandages.…”
Section: Thementioning
confidence: 99%